ZIF‐Mg(OH)2 Dual Template Assisted Self‐Confinement of Small PtCo NPs as Promising Oxygen Reduction Reaction in PEM Fuel Cell. Issue 32 (8th July 2022) - Chen, Zhenyu; Hao, Chao; Yan, Bowen; Chen, Qiuyan; Feng, Huiyan; Mao, Xiaoqing; Cen, Jianmei; Tian, Zhi Qun; Tsiakaras, Panagiotis; Shen, Pei Kang
Abstract: Traditional calcination usually causes sintering of Pt, which diminishes Pt exposure in proton exchange membrane fuel cell (PEMFC) electrodes. In the present work, a facile self‐confined method for synthesizing highly dispersed PtCo‐alloy on Co, N co‐doped mesoporous carbon (PCN‐MC) is developed via a dual‐template strategy. Owing to the co‐confined effect of Zn in the bimetallic zeolite‐based imidazolate framework (ZIF) and Mg(OH)2 template, ultra‐fine 2.7 nm PtCo‐alloy with 2–3 atomic‐layer Pt‐skin nanoparticles are obtained. By adjusting the Co/Zn feeding‐ratio in the bimetallic ZIF at 8/7, the alloying degree and nanoparticle size are optimized to achieve an outstanding oxygen reduction reaction activity with a high mass activity (MA) of 0.956 A mgPt −1 in 0.1 m HClO4, about 7.5‐fold of that of commercial Pt/C. Furthermore, notable durability is also achieved with 81% retention of the initial MA after 30k cycles conducted between 0.6–1.0 V (versus reversible hydrogen electrode). These features are also verified by a H2 –Air fuel cell test with an excellent combination of mass activity, power density, and durability. This strategy provides a feasible route for the large‐scale synthesis of highly‐dispersed PtCo‐alloy catalysts. Abstract : A self‐confined strategy to synthesize highly dispersed PtCo/meso‐Co‐N‐C is employed. The co‐confinement of Mg(OH)2 and Zn in a zeolite‐based imidazolate framework effectively restrains PtCo growth. The Co/Zn ratios are optimized to achieve maximum oxygen reduction reaction (ORR) performance. The PtCo/CoNC exhibits outstanding ORR activity and durability when applied in a proton exchange membrane fuel cell.